When Free Exercise and Nonestablishment Conflict - Greenawalt, Kent (Harvard University Press, 2017)
"Congress shall make no law reflecting an establishment of religion or prohibiting the free exercise thereof." The First Amendment aims to separate church and state, but Kent Greenawalt examines many situations in which its two clauses—the Nonestablishment Clause and the Free Exercise Clause—point in opposite directions. How should courts decide?